(untitled) (Al-Qamar, 2020)
The concept of magic is found in almost every society of the world and in every language, and people of every society have participated in its editing and development in different times, so there is literature available on magic in all famous languages. In this article we will study the prohibition of magic, in the Holy Quran and Bible. Magic has been forbidden since the dawn of mankind, and it has been deprecated. As is evident from verses of Holy Quran.